First international and after: Political writings Vol.3 - David Fernbach; MARX (Karl) (England: Penguin Books, 1981)
Volume 3: The First International and After: The crucial texts of Marx$1 (Bs later years$1 (Bnotably The Civil War in France and Critique of the Gotha Programme$1 (Bcount among his most important work. These articles include a searching analysis of the tragic but inspiring failure of the Paris Commune, as well as essays on German unification, the Irish question, the Polish national movement and the possibility of revolution in Russia. The founding documents of the First international and polemical pieces attacking the disciples of Proudhon and Bakunin and the advocates of reformism, by contrast, reveal a tactical mastery that has influenced revolutionary movements ever since.s
Keywords: Karl Marx; Economics